Effects from supplementary feeding of bamboo powder in perinatal period on farrowing process, serum biochemical indexes, and fecal microbes of sows and offspring piglets - Dai, Fawen; Lin, Tao; Huang, Xia; Shi, Xiaolin; Yang, Yaojun; Nong, Xiang; Zuo, Jianjun; Liu, Hui (Frontiers in Microbiology, 2023)
Introduction This study was conducted to explore the effects of supplementary feeding of bamboo powder on the physical parameters of sows during the perinatal period of 7 days ± in parturition, including farrow duration, serum biochemical indexes, fecal physicochemical indexes, and microbial flora. Methods Thirty pregnant sows were randomly divided into three groups: the control group was fed a basal diet, TRE1 group and TRE2 group were fed a basal diet supplemented with 30 g d−1 and 60 g d−1 bamboo powder, respectively. Multiple parameters of sows and offspring piglets were determined. Results The contents of serum total cholesterol and triglyceride of sows in TRE2 group were significantly lower than those in the control group. The contents of serum malondialdehyde of sows in TRE2 and TRE1 groups were significantly lower than that in control group. The water content of sow feces in TRE2 group was significantly higher than that in control group, and the pH values of sows in TRE2 and TRE1 groups were significantly higher than that in control group. The richness index (Chao) of sow fecal bacterial community in TRE2 group was significantly lower than that of the control group, and the Ace and Sobs indexes tended to be lower than those of the control group. At the phylum level, the relative abundance of Actinobacteriota in the feces of sows in TRE2 group was significantly lower than that of the control group, while that of Fusobacteriota in the feces of suckling piglets in TRE2 group tended to be lower than that of the control group. At the genus level, among the Top10 dominant bacteria, the relative abundance of Tissierella in the feces of sows in TRE2 group was significantly lower than that of the control group while that of Fusobacterium in the feces of suckling piglets in TRE2 group tended to be lower than that of the control group. The relative abundance of Clostridium_sensu_stricto_1, Terrisporobacter, Turicibacter, and Tissierella in the feces of sows in TRE2 group was significantly lower than that of TRE1 group (p < 0.05), while Lactobacillus tended to be higher than that of TRE1 group (p < 0.10). Discussion The results suggested that supplementary feeding 60 g d−1 bamboo powder could increase the water content in the feces of sows, reduce the oxidative damage, and tend to reduce the relative abundance of opportunistic pathogenic Fusobacterium for suckling piglets, while it reduced the fecal microbial diversity of sows.